Membaca Kutika sebagai Sistem Tanda: Kajian Semiotika Roland Barthes dalam Konteks Budaya Lokal dan Perspektif Komunikasi Islam: Kajian Semiotika Roland Barthes dalam Konteks Budaya Lokal dan Perspektif Komunikasi Islam - Putri, Nivyra Gaulia; Fatimah, Fatimah (Palakka : Media and Islamic Communication, 2025)
This study examines Kutika Ugi’ Sakke Rupa as a system of signs within Bugis culture by applying Roland Barthes’ semiotic framework of denotation, connotation, and myth. Using a qualitative method, this research is conducted as cultural text analysis based on library research, with the kutika manuscript written in Lontara script as the primary data. The findings show that, at the denotative level, kutika functions as a practical guide for determining auspicious and inauspicious times; at the connotative level, it reflects Bugis cosmological values emphasizing prudence and harmony with nature; and at the level of myth, it reinforces Bugis spiritual identity. This study contributes to existing scholarship by demonstrating that kutika operates not merely as a traditional calendar but as a cultural sign system that can be understood from the perspective of Islamic communication as a form of ‘urf ṣaḥīḥ, as long as it is not believed to determine destiny absolutely.